Diet, physical activity, and emotional health: what works, what doesn't, and why we need integrated solutions for total worker health - Iffath U. B. Syed (BMC, 2020)
Abstract Background Current research advocates lifestyle factors to manage workers' health issues, such as obesity, metabolic syndrome, and type II diabetes mellitus, among other things (World Health Organization (WHO) Obesity: preventing and managing the global epidemic, 2000; World Health Organization (WHO) Obesity and overweight, 2016), though little is known about employees' lifestyle factors in high-stress, high turnover environments, such as in the long term care (LTC) sector. Methods Drawing on qualitative single-case study in Ontario, Canada, this paper investigates an under-researched area consisting of the health practices of health care workers from high-stress, high turnover environments. In particular, it identifies LTC worker's mechanisms for maintaining physical, emotional, and social wellbeing. Results The findings suggest that while particular mechanisms were prevalent, such as through diet and exercise, they were often conducted in group settings or tied to emotional health, suggesting important social and mental health contexts to these behaviors. Furthermore, there were financial barriers that prevented workers from participating in these activities and achieving health benefits, suggesting that structurally, social determinants of health (SDoH), such as income and income distribution, are contextually important. Conclusions Accordingly, given that workplace health promotion and protection must be addressed at the individual, organizational, and structural levels, this study advocates integrated, total worker health (TWH) initiatives that consider social determinants of health approaches, recognizing the wider socio-economic impacts of workers' health and wellbeing.